Few more hidden variables which would fortify person centred approach of self-regulated learning (Canadian Medical Education Journal, 2019)
Upon reading the original article on person centred approach in self regulated learning, I felt that few more hidden variables tend to operate in the process of self-regulated learning. The motivation level of students and its regulation determines the willingness of students invested towards the process and it is imperative for the educators to gauge this process during mentoring sessions. Similarly, understanding the role of epistemological beliefs could also be considered as a pertinent role player in person centred apporach. I hope that this letter, penned from the existing literature and from personal experiences, would serve as an effective adjuvant to the original article.